2007
DOI: 10.1016/j.jhazmat.2007.01.095
|View full text |Cite
|
Sign up to set email alerts
|

Dry scrubbing of acid gases in recirculating cyclones

Abstract: This paper describes a laboratory-scale study on the use of recirculating cyclones as reaction chambers for dry scrubbing of gaseous HCl with solid slaked lime particles. This gas cleaning system combines a numerically optimized reverse flow gas cyclone (RS VHE geometry) with a straight-through cyclone concentrator, which simultaneously increases the capture of the solid particles and promotes their partial recirculation. A laboratory-scale study was undertaken to test this technology and to compare its perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The XRD pattern shows that Ca(OH) 2 , CaCl 2 ·2H 2 O, and Ca(OH)Cl were present in the sample. Most of the studies reported in literature [11][12][13] assume that CaCl 2 ·2H 2 O and Ca(OH)Cl are both chlorinated products of the reaction between Ca(OH) 2 and HCl, according to the following equation:…”
Section: Sample Characterizationmentioning
confidence: 99%
“…The XRD pattern shows that Ca(OH) 2 , CaCl 2 ·2H 2 O, and Ca(OH)Cl were present in the sample. Most of the studies reported in literature [11][12][13] assume that CaCl 2 ·2H 2 O and Ca(OH)Cl are both chlorinated products of the reaction between Ca(OH) 2 and HCl, according to the following equation:…”
Section: Sample Characterizationmentioning
confidence: 99%
“…(17). The equation describing the mass balance of the gaseous reactant in the ith CSTR takes the form:…”
Section: Recirculating Cyclones (Recyclone Systems)mentioning
confidence: 99%
“…(9) in the previous equation, and C A out i in the equation of the material balance of the solid reactant [Eq. (17)] and knowing that (…”
Section: Recirculating Cyclones (Recyclone Systems)mentioning
confidence: 99%
See 1 more Smart Citation
“…It was finally concluded that incorporation of various droplet interactions could refine the models for better prediction of removal efficiency. Chibante et al (2007) investigated on the dry scrubbing of gaseous HCl with solid slaked lime particles using recirculating cyclones as reaction chambers. This gas cleaning system basically combined a numerically optimized reverse flow gas cyclone with a straight-through cyclone concentrator that simultaneously increased the capture of the solid particles and partial recirculation.…”
mentioning
confidence: 99%